A fractal-based model to improve cooperation among physicians in distributed healthcare information systems / Nawzat S. Ahmed - Ahmed, Nawzat S. (2013)
The system cooperation has become an important issue and used in healthcare systems to exchange information and ideas among physicians. Healthcare systems generally have distributed structures and consist of individual centres supported by autonomous Healthcare Information Systems (HISs). HISs serve as bases for exchanging healthcare information among physicians within the hospital environment. In the available literature, many studies have developed cooperative HISs models to improve cooperation among physicians in sharing patient information, as depositories to provide better services. However, none of these studies focused on the development of cooperative HISs models to improve physician skills to provide quality care to patients. In most developing countries, such as Iraq, cooperation among physicians in sharing information and skills in the patient treatment within the hospital environment is still very poor. Such poor cooperation can lead to insufficient outcomes where lack of medical skills yield disastrous consequences. In this study, a fractal approach has been used in proposing the Fractal-based Healthcare Information System (FHIS) model to improve cooperation among physicians in sharing information and skills within same and between different hospitals. The data collection has been carried out at two government hospitals in Kurdistan region of Iraq, as a case study. The mixed method approach, which combines questionnaires and semi-structured interviews, conducted, (1) to determine the current levels of cooperation among physicians with regard to sharing information and skills in the patient treatment, within selected Iraqi hospitals, (2) to determine factors that affect such cooperation among physicians, (3) to determine how the activities of Research and Development (R&D) units affect cooperation among physicians, and (4) to develop a FHIS model intended to improve cooperation among physicians with regard to the sharing of information and skills. Questionnaires were distributed among one hundred physicians; however, only eighty one questionnaires were completed and considered for analysis. Ten specialist physicians were selected for semi-structured interviews. Results showed an availability lack of cooperation among physicians. This lack of cooperation occurred because of significant factors, such as system units wish to maintain autonomy; a flexible cooperative approach is not the norm in the developing of cooperative HISs; large amounts of data are difficult to manage and control in manual and centralized systems; new knowledge is not acquired in a timely manner; physicians work independently; and R&D unit activities are weak. This study also concluded that a positive relation exists between R&D unit activities and cooperation among physicians using a simple regression analysis (F(1,79)=7.230). The FHIS has been implemented in participating hospitals to evaluate the system usability and the effect of this system in improving cooperation among physicians. The mixed method of questionnaires and semi-structured interviews were conducted in the evaluation process. Results indicated that the FHIS is satisfactorily (system usability scale scores = 75.04) and the cooperation among physicians in sharing healthcare information corresponds to significant improvements in skill using a paired samples T test (t(55)=-20.486). Further research needs to consider the cooperation between administrative and financial sections as well as the data-viewing privacy of physicians.